Relations between basic anthropometric indexes and selected elements of maintain balance abilities in high level fencers - Starosta, W.; Markiewicz, G.; Pawlowa-Starosta, T. (Journal of Combat Sports and Martial Arts, 2012)
The aim of the work was to: 1. Define the relation between the basic antropometric indexes and the age, training period, sport class and specialisation of the fencers. 2. Search relations between the basic antropometric indexes and the selected abilities to maintain balance. Material and methods. There were 87 fencers taking part in the researches. Those investigated belonged to the youth up to the (masters) champion sport class, and were in the starting training period. In order to conduct balance measurements a device composed of a posturographic platform connected to a computer with a monitor — registering the translocation of the body`s centre of gravity, was applied. The examination was composed of three test tasks: 1. The ability to maintain the stable body position with an eyesight control. 2. Assessed the behaviour of this centre with the eyes closed. 3. Applied feedback on the basis of which the examined tried to maintain a light spot in a small square displayed on the monitor through the adequate "platform adjustment". Results. Significant relations were observed between: the height and the body mass (0.67); the age and the training period (0.67); the performance of the task with opened and closed eyes; the performance of the task with open eyes (0.68); the performance of the task with open eyes (DC) and closed eyes (PPR): 0.43; performance of the task with open eyes (DC and PPR): 0.67; execution of the task with open eyes (DC) and closed eyes (PPR): 0.71. Conclusions. High correlation coefficients occurred, however, between the results of the particular tasks evaluating the abilities to maintain balance defined through coefficients of total length and the area of the extended surface. No statistically significant correlation between the basic anthropometric indexes and selected elements of abilities to maintain balance was ascertained.